Intervensi Diet pada Pencegahan Obesitas Anak - Devi Mutiara Jasmine (Jurnal Ilmu Medis Indonesia, 2022)
Purpose: This study aims to review the existing literature regarding dietary interventions for the prevention of obesity in children and their effectiveness. Metode: A literature search was carried out using search engines PubMed Central, Elsevier and Google Scholar, limiting the last 10 years to articles from 2011 to 2021. Result: Most of the programs/interventions carried out focused mainly on school-based intervention approaches, community-based interventions, interventions through mass media and food sector interventions. In its own application, this control is divided into two parts, namely micro and macro policies. Limitation: This article is only a review of several other articles, not doing research directly. Contribution: With proper examination, it is hoped that cases of children’s obesity can be prevented by some dietary interventions.